The Québec-United States Relationship
XXXIV, 426 p. 15 illus., 13 illus. in color.
Keywords: This book provides an essential and necessary update on the evolution of Québec democracy and its politics – specifically its engagement with the United States across many issues and areas… It is certainly timely, and offers considerable food for thought. Happy reading! -Guy Lachapelle, Professor, Political Science Concordia University Québec’s engagement with the United States is the most significant and consequential point of interaction amongst all its international activities. This volume explores the many ways in which Quebec engages with the United States, including political exchange, border issues, trade, business and investment, transportation, immigration, cultural links and identity, the role of energy transmission and natural resources, and environmental considerations. As a sub-national actor pursuing a wide range of paradiplomatic bilateral and multilateral initiatives directly involving the U.S., the book both explores and explains what, when, why and how Québec has chosen to engage the United States while examining the fundamental issues that lie at the heart of the relationship. This is an open access book. Christopher Kirkey is Director of the Center for the Study of Canada and Institute on Quebec Studies at State University of New York Plattsburgh. Frédérick Gagnon is Full Professor, Holder of the Raoul Dandurand Chair in Strategic and Diplomatic Studies, and Director of the Center for United States Studies and of the Center on Multidimensional Conflicts at the University of Québec in Montreal. He is also Global Fellow at the Canada Institute of the Wilson Center. Stéphane Paquin is Jarislowsky Chair in Trust and Political Leadership (UQTR-ENAP) and tenured Professor at the École nationale d’administration publique (ENAP) where he is the director of GERIQ (Groupe d’études et de recherche sur l’international et le Québec).